Minat Berkunjung Kembali Pada Sangkan Resort Aqua Park Kuningan - Dikdik Harjadi (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
Competition in the amusement rides industry is increasing in line with the popularity of this destination. Industry players are competing to create value or privilege among the many rides to play in Indonesia. This study aims to determine the physical attributes, interactions with customers, interactions with employees, customer satisfaction and interest in returning. A total of 100 visitors were taken as samples by accidental sampling. The data analysis technique used Structural Equation Modeling (SEM) with AMOS. The results showed that physical attributes, interactions with customers and interactions with employees had a positive effect on customer satisfaction. Physical attributes and interactions with customers, as well as customer satisfaction have a positive effect on interest in returning.